Clinical Course of Cancer Patients With COVID-19: A Retrospective Cohort Study. Issue 1 (2nd November 2020) - Alpert, Naomi; Rapp, Joseph L; Marcellino, Bridget; Lieberman-Cribbin, Wil; Flores, Raja; Taioli, Emanuela
Abstract: Background: Complications in cancer patients with coronavirus disease 2019 (COVID-19) have not been examined. This analysis aimed to compare characteristics of COVID-19 patients with and without cancer and assess whether cancer is associated with COVID-19 morbidity or mortality. Methods: COVID-19–positive patients with an inpatient or emergency encounter at the Mount Sinai Health System between March 1, 2020, and May 27, 2020, were included and compared across cancer status on demographics and clinical characteristics. Multivariable logistic regressions were used to model the associations of cancer with sepsis, venous thromboembolism, acute kidney injury, intensive care unit admission, and all-cause mortality. Results: There were 5556 COVID-19–positive patients included, 421 (7.6%) with cancer (325 solid, 96 nonsolid). Those with cancer were statistically significantly older, more likely to be non-Hispanic Black and to be admitted to the hospital during their encounter, and had more comorbidities than noncancer COVID-19 patients. Cancer patients were statistically significantly more likely to develop sepsis (adjusted odds ratio [ORadj ] = 1.31, 95% confidence interval [CI] = 1.06 to 1.61) and venous thromboembolism (ORadj = 1.77, 95% CI = 1.01 to 3.09); there was no statistically significant difference in acute kidney injury (ORadj = 1.10, 95% CI = 0.87 to 1.39), intensive care unit admissions (ORadj = 1.04, 95% CI = 0.80 to 1.34), or mortality (ORadj = 1.02, 95% CI = 0.81 to 1.29). Conclusions: COVID-19 patients with cancer may have a higher risk for adverse outcomes. Although there was no statistically significant difference in mortality, COVID-19 patients with cancer have statistically significantly higher risk of thromboembolism and sepsis. Further research is warranted into the potential effects of cancer treatments on inflammatory and immune responses to COVID-19 and on the efficacy of anticoagulant therapy in these patients.